Hadhrami Networks and Colonial Legacies in Marriage Discourses of the Indies - Taufik, Egi Tanadi; Bisri, Hasan (Religió Jurnal Studi Agama-agama, 2024)
This study draws the relationship between the European colonial legal administration and the discourse of Islamic law in Indonesia by focusing on specific historical contexts from the Dutch East Indies to modern-day Indonesia. Particularly, it tries to understand how colonial behavior of anti-miscegenation relates to the modern customary law of endogamy among Indonesian Bā ‘Alawi under kafā‘a doctrine. This study applies qualitative methods to highlight the legal history of Muslim endogamy focused on the Hadhrami-origin ‘Alawiyyīn in Indonesia. The initial section discusses the institution of marriage law in Islamic classical sources and the narrative of particular ethnical-national supremacy. It argues that the colonial regime passed the legislation of anti-miscegenation laws to support endogamic marriage, intensify inter-racial tensions among indigenous people, and dehumanize mixed-blooded children. That legislative enactment is based on certain colonial legal mechanisms passed to maintain order between different ethnicities and races which were then readopted among Hadhrami Muslims to popularize kafā‘a doctrine. Hence the constructed idea of “pernikahan sekufu” or kufū’-based marriage was later associated with the intra-ethnical marriage, especially among the sharīf/sharīfa which withheld the claim of their superior lineage as descendants of the Prophet.